The Role of Attributional Style in a Call Centre Environment - Fulcher, Patricia Ann (Auckland University of Technology, 2007)
This study explored the relationship between attributional style and the performance of front line service staff in a call centre environment. Attributional style was evaluated using a well recognised method (Seligman's Attributional Style Questionnaire). This was the first time that the Seligman's Attributional Style Questionnaire (SASQ) has been used in a New Zealand context. Performance was calculated using five independent measures. These measures have been used for several years by the company at the centre of our study as an objective measure of Call Centre Representative (CCR) performance. The association between attributional style and performance was then examined using a combination of Analysis of Variance (ANOVA) and co relational analysis. People have different ways of reacting to adversity such as failure, rejection or a high-pressure situation. The ability to succeed is closely tied to the ability to handle adversity (DeCarlo et al., 1997; Seligman & Schulman, 1986; Boone, 2000). Research has supported the common sense view that optimistic beliefs can be self-fulfilling prophecies (Sujan, 1999a; Porter, 2000; Furnham et al., 1994). Hundreds of studies have revealed the benefits of optimism such as increased motivation, superior achievement (in various areas e.g. work, school and sports), elevated mood and well-being, and better physical health (Seligman et al., 1990; Seligman et al., 1986). Furthermore, individuals can learn to reduce negative ways of thinking and become more optimistic when it is appropriate (Satterfield et al., 1997; Eronen et al., 1999; Bohart, 2002).Call centres are not new phenomena, however they have become a growth industry in the private and public sector over the last decade (Creagh, 1998). The following definition of call centres was used by Gilmore and Moreland; "A physical or virtual operation within an organisation in which a managed group of people spend most of their time doing business by telephone, usually working in a computer-automated environment." (2000, pg 4)Due to the size and the complexity of tasks undertaken within call centres, there is a growing need for empirical findings to broaden understanding of how to best manage call centres and how to optimise the utilisation of human capital (Feinberg et al, 2000).This cross-sectional study assesses the performance of Call Centre Representatives (CCRs) in a New Zealand based call centre and explores whether there is an association with the Seligman's Attributional Style Questionnaire (SASQ).It was found that the performance measure for soft skills varied significantly when ranked by a measure of optimism. The performance measures considered in this study focus mainly on technical competency and task efficiency, and were therefore not well explained by attributional style. Future research should investigate pre-testing for soft skills at recruitment, interventionist training on attitude and whether that translates into improved soft skill performance, and the reassessment of current call centre performance measurements.
Keywords: Call centers; Employees; Attitudes; Business